LIMITATION OF RELIGIOUS FREEDOM IN RESPONSE TO COVID-19: FROM PUBLIC HEALTH REGULATIONS TO DISCRIMINATORY POLICIES - Hanif Nur Widhiyanti; Anak Agung Ayu Nanda Saraswati (Diponegoro Law Review, 2021)
A number of regulations and policies implemented by some countries regarding the limitations of freedom to manifest religion or belief have been highly debated since the Covid-19 pandemic. Many argue such policies are discriminative and inconsistent with human rights law. Thus, this paper aims at analyzing the concept of human rights in the implementation of religion manifestation during the pandemic, and investigating how states implement policies according to the international human rights legal framework. This normative research which uses comparative and conceptual approach concludes that policies established by states in general can be legitimized on several conditions, among others for public health concerns. In addition, the proportionality and the non-discrimination principles need to be applied accordingly.